Stabbing and safeguarding in children and young people: a Pan-London service evaluation and audit. Issue 7 (5th June 2013) - Apps, John R; Williams, Carrie; McGuinness, Anne; Gabbie, Susie; Sutcliffe, Alastair G
Objectives: To characterize paediatric presentations of stabbing to emergency departments across London and to audit existing referral rates to the police and social services against the new standard set by the General Medical Council. Design: Retrospective multi-centre service evaluation/audit. Setting: All emergency departments within London. Participants: Patients under 18 years of age presenting to emergency departments with non-accidental stabbing between 1 April 2007 and 30 April 2009. Main outcome measures: Patient age, nature of assault, assailant, injuries and management. Rates of documented referral to police and social services, as mandated by GMC guidance. Results: A total of 381 presentations were identified from 20 out of the 32 hospitals in London, 160 of whom were less than 16 years old. The majority were seen only by emergency department staff and only a minority (28%) were admitted. Three died in the departments. A knife was the commonest weapon and the limbs the most common site of injury. Referrals to police were documented in only 30% of patients (43% if <16 years old) and to social services in 16% (31% if <16 years old) of those discharged. In the majority, there was no documentation (police 64%, social services 79%). Conclusions: A significant number of paediatric stabbings present to emergency departments across London. The majority of these are discharged directly from departments. Of those discharged, documentation regarding referral rates to Police and Social Services was poor, and documented referral rates low. This study covered a period prior to the introduction of new General Medical Council guidance and a repeat audit to assess subsequent documented referrals is required.